¿Cómo es la evaluación en un curso que sigue la metodología ABP? - Morales Bueno, Patricia (2013)
This article focuses on the different ways in which the concepts of teaching and learning are conceived. It also defines the conception on which the educational view of the PBL is based, and how it determines its learning goals. Likewise, it shows how evaluation strategies are bonded to each of the stages in the PBL process, noting their features and the relation with learning goals of the methodology.